The Relationship Between Optimism and Peer Support on the Resilience of Adolescents Who Have Lost A Parent - Hastuti, Jesina; Ahyani, Latifah Nur (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to empirically examine the relationship between optimism and peer support on the resilience of adolescents who have lost a parent. Participants were adolescents aged 12-18 who had lost a parent due to the death of one or both (orphans, orphans, orphans). This study used a quantitative correlation method. The sampling technique used was quota sampling, with a sample size of 100 respondents. Data collection tools included resilience scales, optimism scales, and peer support scales. The results of the minor hypothesis analysis on the optimism and resilience variables yielded an rx1y of 0.662 and a p-value of 0.000 (p<0.01), with an effective contribution of 43.8%. This indicates a highly significant positive relationship between optimism and resilience in adolescents who have lost a parent, thus accepting the first hypothesis. The minor hypothesis analysis on the peer support variable and resilience yielded an rx1y of 0.581 and a p-value of 0.000 (p<0.01), with an effective contribution of 33.7%. This indicates a highly significant positive relationship between peer support and resilience in adolescents who have lost a parent, thus accepting the second hypothesis. The correlation coefficient for the three variables, rx12y, was 0.743 and a p-value of 0.000 (p<0.01), with an effective contribution of 55.3%. This indicates that the major hypothesis is accepted, indicating a highly significant relationship between optimism and peer support and resilience in adolescents who have lost a parent.